Immigrant Occupational Attainment: Assimilation and Mobility over Time - Green, David A. (Journal of Labor Economics, 1999)
This article compares immigrant and native‐born male occupational distributions in Canada in the 1980s. Three questions are addressed: (1) How do immigrant and native‐born occupational distributions differ? (2) Are immigrants more occupationally mobile? and (3) How do immigrant occupations and mobility relate to characteristics used in immigrant selection? Results indicate that immigrants are more skilled, but this declines across successive cohorts. Immigrants are more occupationally mobile even long after arrival, indicating immigration may contribute to a more flexible labor force. Immigrants who are not assessed on their skills or are not fluent at arrival are less occupationally mobile.